Solvent Optimization For Genistein Isolation Of â€œRotten Tempeâ€ By High Performance Liquid Chromatography Method - Cucun Alep Riyanto; Hartati Soetjipto (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2017)
Genistein is a soy isoflavone that has been known have anticancer properties. The aim of this research is to determine the right combination of solvents to extract isoflavones in rotten tempe and determine the genistein content of the extraction process by the High Performance Liquid Chromatography (HPLC) method. Isoflavone extraction process was done using a mixture of methanol and chloroform solutions. Isoflavone extracts obtained will be analysed using High Performance Liquid Chromatography (HPLC) method to determine the content of genistein. The optimum isoflavone extract was obtained from chloroform:methanol (10:1 v/v) solvent ratio. Where as the highest contents of genistein from the 4th day â€œrotten tempeâ€ as 26.199 ± 25.146 (mg/g).